Precarious Japan - Allison, Anne, 1950- (Chronicles of the New World order., 2013)
Precarious Japan reflects on how the Japanese are experiencing insecurity in the contemporary era of nagging recession, irregular labor, nuclear contamination, and a shrinking overall population with more and more elderly.